Dados governamentais abertos: métricas e indicadores de reúso - Patricia Nascimento Silva (2018)
Since the open government initiatives initiated by the USA in 2009, several countries have developed open data policies and action plans to stimulate the reuse of public sector information. Considering this outline, the research was motivated to the challenge of using open government data (OGD), respecting the legal requirements, from the point of view of products and services. The objective of this thesis was to propose a model of evaluation of the OGD in the Federal Public Administration of Brazil, based on metrics and indicators international to subsidize the evaluation of the reuse of brazilian OGD. The research methodology was divided into three stages; its first stage used documentary research to identify the information policies present in Brazil and information categories of the applications made available in the Governo Federal Application Guide. In the second stage, the models and metrics of other countries were identified with respect to the evaluation of OGD reuse. In the third empirical stage of the research, the DGABr metric, based on the Brazilian context, was proposed to measure the reuse of OGD in the public administration of Brazilian. A proof of concept of the metric DGABr was performed in a Federal Public Administration body, identifying a positive result in the evaluation of the OGD by the metric. The results of the research show that the reuse is incipient due to the amount of data available in the Brazilian Open Data Portal. In addition, the lack of continuity of governmental actions and the unavailability of portals hinder reuse. The experience of other countries with regard to the evaluation of the OGD directed the creation of the Brazilian metric by the thesis, but the legislation and the information policies of each country directly influence the way in which the OGD are made available and, consequently, in its reuse. The DGABr metric provides citizens with ways to evaluate the DGAs available and contributes to the appropriation of the information made available in datasets, applications and portals. The proof of concept made with the metric allowed to validate the proposed dimensions and the potential reuse indicator of the OGD. The DGABr is an initial proposal to evaluate the Brazilian OGD and their reuse and should evolve along with the information policy of Brazil with respect to data recently opened in May 2016 by Decree nº. 8.777.